Perioperative Fluid Management and Use of Vasoactive and Antithrombotic Agents in Free Flap Surgery: A Literature Review and Clinical Recommendations - Brinkman, J. Nick; Derks, Lieke H.; Klimek, Markus; Mureau, Marc A.M. (Journal of Reconstructive Microsurgery, 2013)
Learning Objectives After reading this article, the participant should be able to (1) outline the rationale for different perioperative types of fluid therapy in free flap surgery and identify the methods considered best for flap survival; (2) understand the current views on the use of vasoactive agents and consider its possible safe use; (3) compare the most commonly used intraoperative and postoperative anticoagulant therapies and identify the risks and benefits associated with each.Background Free flap surgery has become a reliable and efficient method for reconstruction of complex soft tissue and bony defects. Despite high success rates, free flap failure remains an important concern. A review of the literature was conducted on nonsurgical factors that may contribute to flap failure or success. Various anesthesiological and anticoagulant methods are applied in free flap surgery, but for the ideal approach there is no consensus. This article provides clinical recommendations on perioperative fluid management and the use of vasoactive and antithrombotic agents and offers a balanced view on the risks and benefits.
Keywords: microsurgery; reconstructive surgery; anesthetic management; fluid therapy; vasoactive agents; antithrombotic agents; flap failure